Adaptive responses of animals to climate change are most likely insufficient - Radchuk V; Reed T; Teplitsky C; van de Pol M; Charmantier A; Hassall C; Adamik P; Adriaensen F; Ahola MP; Arcese P; Aviles JM; Balbontin J; et al. (NATURE PUBLISHING GROUP, 2022)
Biological responses to climate change have been widely documented across taxa and regions, but it remains unclear whether species are maintaining a good match between phenotype and environment, i.e. whether observed trait changes are adaptive. Here we reviewed 10,090 abstracts and extracted data from 71 studies reported in 58 relevant publications, to assess quantitatively whether phenotypic trait changes associated with climate change are adaptive in animals. A meta-analysis focussing on birds, the taxon best represented in our dataset, suggests that global warming has not systematically affected morphological traits, but has advanced phenological traits. We demonstrate that these advances are adaptive for some species, but imperfect as evidenced by the observed consistent selection for earlier timing. Application of a theoretical model indicates that the evolutionary load imposed by incomplete adaptive responses to ongoing climate change may already be threatening the persistence of species.